As plantações de hortelã e as dinâmicas socioculturais da fronteira: memórias, trajetórias e estranhamentos em Mercedes (Oeste do Paraná 1960-2009) - Backes, Gilson (2009)
This research probes experiences lived in the socio-cultural dynamics of the mint plantations in the borough of Mercedes, extreme West of Paraná, since 1960. We analyzed, by the ways of memory, the labor relations, the ways of life, the tensions and the cultural differences constituted around this economic activity which had been practiced through different workers that migrated to that region and worked on there. The study of memories and social trajectories let us to apprehend a past reality that was more complex than the one which was told by the memorial and academy literatures; that defends hegemonic concepts or ideas, which are part of the social life of this region. These trajectories evinced that the occupation of the region didn t has constituted by a planned and consensual form like it was divulged, because the most part of the migrant workers arrived and went out without having a sense of belonging. When different people arrived; by diverse places and times, differences and socio-cultural conflicts became latent, as it was verified in oral telling reported by people who remains in that region. This research sought, then, to study the historical events of the formation of this border space with a recent occupation, probing the formation of your social landscape, which passed by intense and deep changes in that period. In the dynamically of the conflicts, relations and social problems of pertain, memories became primordial to the interpretation of this frontier, where the increasing multiple tensions and instituting deep damages to the nature